Eu não disse isso: uma análise do funcionamento da autoria nas mensagens compartilhadas de Caio Fernando Abreu e Clarice Lispector no facebook - Rosin, Pâmela da Silva (Universidade Federal de São Carlos, 2013)
In this term paper, we describe and analyze more systematically the questions that came up from the research project Práticas de escrita e de leitura na rede: uma análise das mensagens compartilhadas e dos procedimentos de sua formulação linguístico-discursivas, developed during our graduation, in which we study a kind of peculiar and current text, which presents itself as "phrases", some taken from literary works, which are to circulate autonomously in social networking pages, in particular, on Facebook. This operation (production, circulation and reception) implies certain changes in the practices of writing and reading today. Regarding this and its autonomous functioning and its particular characteristics, we classified these as shared messages. These are highlighted statements, especially of literary works, which are selected, adapted , added images , which have the effect of modifying to some extent the "meaning" of these statements . These messages are posted by the users on their personal pages or murals friends and even in communities or pages. To select these messages we use the homepage O Mundo de Caio Fernanado Abreu e Clarice Lispector that functions as a repository of shared messages of these two contemporary authors. In the course of our analysis in scientific research, one of the changes in which we are faced, and which we focus in this term paper, is relative to the operation of authorship in the composition of such messages. Several procedures for assigning authorship we see being employed in these shared messages, such as the mistaken attribution of authorship, the use of phrases in the source texts that would not necessarily part of the "work " of an author (interviews and letters), the attribution of authorship to the entire message and not just the phrase taken from the work of one author, etc. To identify this specific operation of authorship , for our analysis, we adopted as a research resource not only shared messages , but also the lifting of comments from readers who recognize the authorship, misattribution criticize, evaluate the text according to another scheme reception (not as a literary work , but as self-help ). For our analysis, we rely on theoretical principles of Discourse Analysis and Cultural History of Reading, based on both theories argue about the changes in the forms of production and circulation of texts. With our work we hope to contribute to the research on the practices of writing and reading today, so we raise some evidence of this new reader/author who emerges with the new digital technologies.
I didn't say that: an analysis of the functioning of authorship in the shared messages by Caio Fernando Abreu and Clarice Lispector on facebook
Keywords: Enunciados destacados; Redes sociais; Análise do discurso; História cultural; Leitura; Detachability; Social networks; Discourse analysis; Cultural history; Reading; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA